2016
DOI: 10.1111/jphp.12575
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and in-vitro/in-vivo evaluation of curcumin nanosuspension with solubility enhancement

Abstract: The Cur-NS significantly increased the water solubility and half-time of Cur, suggesting its potential as a nanocarrier in the delivery of Cur for future clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…High cumulative release concentration is obviously essential in increasing the bioavailability of Curcumin. The release behavior may be induced by improved solubility of Curcumin in water, consistent with the findings of Li [24] and Kumar [25]. …”
Section: Discussionsupporting
confidence: 87%
“…High cumulative release concentration is obviously essential in increasing the bioavailability of Curcumin. The release behavior may be induced by improved solubility of Curcumin in water, consistent with the findings of Li [24] and Kumar [25]. …”
Section: Discussionsupporting
confidence: 87%
“…However, there was no exothermic peak appeared in the thermogram of GNA‐ZN‐NPs, meaning that GNA might transform to an amorphous form after the preparation of nanoparticles. The reason may be that GNA could not rapidly combine into the developing crystal lattice within a limited time in the presence of stabilizers . The degree of the amorphization in GNA‐ZN‐NPs was significantly higher than GNA, which resulted in the reduced crystallinity and the increased solubility.…”
Section: Resultsmentioning
confidence: 99%
“…The reason may be that GNA could not rapidly combine into the developing crystal lattice within a limited time in the presence of stabilizers. [36] The degree of the amorphization in GNA-ZN-NPs was significantly higher than GNA, which resulted in the reduced crystallinity and the increased solubility.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…Curcumin nanosuspension was prepared with solvents of PVPK30 and SDS and curcumin released 84% within 34 h and it showed higher toxicity as well. Pharmacokinetic studies showed that CU-NS quickly reached the tissue organs, suggesting that the formulation is effective; however, toxicity of SDS remains questionable when translated [65]. No other study showed about the toxicity of curcumin or its derivative molecules with or without other compounds and hence further studies is needed to confirm the previous findings.…”
Section: Toxicity Study Of Curcumin Nanocomplexmentioning
confidence: 94%